2010
DOI: 10.1016/j.drudis.2010.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Developments towards antiviral therapies against enterovirus 71

Abstract: Enterovirus 71 (EV71) has emerged as a clinically important neurotropic virus that can cause acute flaccid paralysis and encephalitis, leading to cardiopulmonary failure and death. Recurring outbreaks of EV71 have been reported in several countries. The current lack of approved anti-EV71 therapy has prompted intense research into antiviral development. Several strategies--ranging from target-based chemical design to compound library screenings--have been employed, while others revisited compound series generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 80 publications
(85 reference statements)
0
61
0
1
Order By: Relevance
“…Pretreatment of EV-71 with soluble annexin II resulted in reduced viral attachment to the cell surface (12). However, inhibitors that blocked all of the receptors identified failed to inhibit EV-71 infection completely (13). This may imply the involvement of one or more EV-71 receptors that have yet to be discovered.…”
mentioning
confidence: 98%
“…Pretreatment of EV-71 with soluble annexin II resulted in reduced viral attachment to the cell surface (12). However, inhibitors that blocked all of the receptors identified failed to inhibit EV-71 infection completely (13). This may imply the involvement of one or more EV-71 receptors that have yet to be discovered.…”
mentioning
confidence: 98%
“…5,6 In a previous study, we demonstrated that EV71 accounted for approximately 94Á4% of the fatal cases of HFMD. 7 At present, there are no effective antiviral medications 8 and no prophylactic vaccine against EV71 infection. 9 EV71 was shown to be responsible in China for most of the fatalities associated with severe neurological manifestations ranging from aseptic meningitis to acute flaccid paralysis and brainstem encephalitis in children < 5 years of age.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…Blood samples were obtained on days 1-7 after onset, discharge from the hospital (day [7][8][9][10][11][12][13][14] and the fully recovered stage (defined as 1 month after illness onset), respectively. All samples were collected specifically for this study and were coded to protect confidentiality.…”
Section: Recruitment and Sample Collectionmentioning
confidence: 99%
“…Several reviews have dealt with anti-enterovirus 71 synthetic small molecules [1][2][3][4][5][6][7]. This review gives an overview of 58 natural products (NPs), semi-synthetic NPs and NP-derived compounds from natural sources during the last decade (2005-2015) which exhibit anti-enterovirus 71 (EV71) activities.…”
Section: Introductionmentioning
confidence: 99%